Iberoamérica y sus sistemas de áreas naturales protegidas: El caso de Perú - Morales Hurtado, Jessica; López López, Alejandro (Observatorio Medioambiental, 2004)
With increasing frequency Latin America is taking up the challenge of creating new protected natural areas as bastions of conservation. In the years that separated the Caracas and Durban summits, there was an in increase in successful experiences in administration and in new concepts and management techniques. Every Latin American country provides, within its own social context, different solutions to the problem of rational use of its territory and its system of protecting natural areas. Peru is a emblematic case because of its biological richness, cultural diversity and pioneering initiatives in administering these areas, within the framework of its Master Plan for the National System of Protected Natural Areas, at the present with 56 areas, managed by the General Director of Protected Natural Areas of the National Institute of Natural Resources (INRENA). An examination of these experiences could be useful in other contexts of environmental and administrative work in other systems.
Keywords: Ibero-America; Systems of Protected Natural Areas; Peru; corridors; Cross-border areas